(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Weed management is one of the significant challenges of vegetable tuber crops since weeds pose a remarkable threat to crop productivity in Bangladesh. A field experiment on efficacy of different herbicides for controlling weeds in onion field was conducted during the rabi season of 2024-25 at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Cumilla, Bangladesh. The treatments included pendimethalin 33% EC @ 800 ml ha-1 (T1) applied at the 2–4 leaf stage of weeds, pendimethalin 33% EC @ 1000 ml ha-1 (T2) spraying on soil 1-2 days before transplanting, oxyfluorfen 23.5% EC @ 750 ml ha-1 (T3) spraying at 3-4 day before transplanting, atrazine 50% + mesotrione 5% SC @ 1000 ml ha-1 (T4) & @ 1500 ml ha-1 (T5) spraying at 3-4 day before transplanting, two hand weeding at 25 and 50 days after transplanting (T6) and a control (T7) with three replications. Results revealed significant differences among treatments in terms of weed dry weight, seedling mortality, bulb yield and economic returns. Atrazine 50% + mesotrione 5% SC @ 1500 ml ha-1 (T5) provided the highest weed control efficacy (up to 91%). Pendimethalin, hand weeding and control recorded 0% mortality of onion seedling. Pendimethalin was effective in controlling both broad leaf and narrow leaf weeds. Maximum bulb yield (18.25 t ha-1), the highest gross return (5,47,410 Tk. ha-1) and highest benefit–cost ratio (2.77) was obtained from pendimethalin 33% EC @ 1000 ml ha-1 (T2). In contrast, atrazine and mesotrione based combinations (T4 and T5) caused severe phytotoxicity with seedling mortality exceeding 75%, resulting in low yield (5.94–6.50 t ha-1), negative gross margins and poor BCR values (<1.0). The study concludes that pendimethalin @ 1000 ml ha-1 before transplanting can be the effective and economically viable weed management practice in onion production. J Bangladesh Agril Univ 24(1): 1–13, 2026